Janie face to face - Cooney, Caroline B. (Delacorte Press, 2013)
At college in New York City, Janie Johnson, aka Jennie Spring, seems to have successfully left behind her past as "The face on the milk carton," but soon she, her families, and friends are pursued by a true-crime writer who wants their help in telling her kidnapper's tale.